Perbandingan Kadar Fenolik Total Air Rebusan dan Ekstrak Etanol Daun dan Batang Sawi Langit (Cyanthillium cinereum (L.) H.Rob) - Saputri, Muharni; Yulia, Rahma; Febriani, Yessi; Ginting, Ernawaty; Amara, Saniatul; Zulkhaira, Zulkhaira; Utami, Intan Putri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Sky mustard is one of the herbaceous plants used by the community to treat diseases such as inflammation, malaria and fever. This herbaceous plant is believed to have secondary metabolites such as phenolics which have many functions. The aim of this research was to determine the total content of phenolic compounds in leaves and stems of sky mustard greens (Cyanthillium cinereum (L.) H.Rob). This research is experimental in nature, including collecting plant material, identifying plants, cold extraction using the maceration method using ethanol and boiled water as a solvent, phytochemical screening, and determining the total phenolic content of boiled water and equivalent ethanol extract of leaves and stems (Gallic Acid Equivalent (GAE)) or gallic acid by colorimetric method using reagents Folin-ciocalteu a wavelength of 760 nm using UV-Visible spectrophotometry. The result of phytochemical screening of sky mustard leaves and stems contain alkaloids, steroids, saponins, flavonoids, tannin, glycosides and phenols. The result showed that phenol levels were greater in the leaves than in the stem the ethanol solvents attracted more phenolic compounds than boiling, and the phenol by boiling was higher at 5 minutes at 0,649 mg/g GAE. For phenolic compounds using ethanol solvent, there was a yield of 748,33 mg/g extract.